Controlled synthesis of a catalytically active hybrid metal-oxide incorporated zeolitic imidazolate framework (MOZIF) - Dey, Chandan; Banerjee, Rahul (Chemical Communications, 2013)
A rare hybrid Metal-Oxide incorporated Zeolitic Imidazolate Framework, MOZIF-1, containing tetrahedral Zn(II) and Mo(VI) centres has been synthesized. MOZIF-1 can degrade methyl orange and orange II dyes under visible light. Na-3[PMo12O40] is the source of Mo(VI) in MOZIF-1.